Fenomenologi Komunikasi Generasi Z Dalam Menghadapi Tantangan Konsep Hidup Frugal Living - Qolbiyah, Najmi; Carissa, Venna; Ravabila Juliandra, Vanya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The phenomenology of communication within Generation Z reveals how social interactions and symbolic interpretations play a crucial role in transforming their lifestyle paradigms. This generation, characterized by their ambition, creativity, and individuality, often faces societal pressures associated with hedonism and the Fear of Missing Out (FOMO). However, through direct experiences and effective communication, Gen Z demonstrates a remarkable ability to navigate these challenges and adopt the frugal living concept—a lifestyle focused on financial prudence and long-term goals. This research explores how Generation Z communicates and negotiates meanings within their social contexts to overcome these pressures. By engaging in intentional decision-making and prioritizing sustainable practices, they manage to redefine their identity while countering the negative stereotypes often associated with their generation. The findings suggest that Gen Z's adoption of frugal living goes beyond mere financial savings; it represents a deeper shift towards meaningful living, balancing social expectations and personal values. As a result, this generation not only refutes the stigma of materialism and FOMO but also sets a positive example for future generations. The study underscores the power of communication as a transformative tool, enabling Gen Z to inspire broader societal change toward sustainability and mindful living.